Static Concentrator Photovoltaics Module for Electric Vehicle Applications Based on Compound Parabolic Concentrator - Hoang Vu; Ngoc Hai Vu; Seoyong Shin (Energies, 2022)
Electric vehicles (EVs) and photovoltaics (PVs) are new technologies that will play an important role in the transportation industry over the next decade. Using solar panels on the roofs of cars is one of the simplest ways to reduce fuel costs and increase the mobility of electric vehicles. Solar electric cars can be charged anywhere under the Sun without additional infrastructure, but the problem is the size of the solar panel is limited on the roof and the electricity conversion efficiency of the panel is only 15% to 20%. This means they will not provide significant electricity to EVs. An effective way to increase efficiency is to utilize multi-junction solar cells with concentrator photovoltaic (CPV) technology. The challenge is that the moving sun-tracking mechanism will reduce the stability of the vehicle structure. To solve this issue, in this research, we present a static concentrator photovoltaic system for electric vehicles. This structure is more stable and simpler than CPV systems using sun-tracking mechanisms and thus suitable for car roof application. The CPV system includes solid compound parabolic concentrators (CPCs), three-junction solar cells, and a crystalline Si cell panel. This structure allows for the manufacture of a static CPV with a geometrical concentration ratio of 4× for three-junction cells. The simulation results showed that the module can achieve 25% annual efficiency. Moreover, it can be flexible to meet the requirements of car roof application.